1996
DOI: 10.1002/j.1552-4604.1996.tb04194.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Gender on Pharmacokinetics of Atorvastatin in Humans

Abstract: Atorvastatin is a new 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitor that reduces plasma cholesterol by inhibiting cholesterol synthesis and increasing cellular uptake of low density lipoproteins. The effects of age and gender on the pharmacokinetics of atorvastatin after administration of single 20-mg tablets of atorvastatin were studied in 16 young and 16 elderly volunteers (8 men and 8 women in each age group). Plasma equivalent concentrations of atorvastatin were quantitated by a valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 11 publications
5
36
2
1
Order By: Relevance
“…Moreover, the importance of sex was often overlooked by using only the ''preferred'' sex in pharmacotoxicological studies, the male rat, or worse yet, not even recording the sex of the animal. Nevertheless, in agreement with limited human findings (4,(7)(8)(9), rodent studies observed an aging-and sex-related decline in the in vivo and in vitro metabolism of different classes of drugs and subnormal baseline concentrations of various components of the hepatic drugmetabolizing enzyme system (10)(11)(12). With the identification in the 1980s of the multiple isoforms of P450 (designated with the initial letters CYP) it became apparent that males were more susceptible to aging-induced declines in drug metabolism than were females.…”
supporting
confidence: 89%
“…Moreover, the importance of sex was often overlooked by using only the ''preferred'' sex in pharmacotoxicological studies, the male rat, or worse yet, not even recording the sex of the animal. Nevertheless, in agreement with limited human findings (4,(7)(8)(9), rodent studies observed an aging-and sex-related decline in the in vivo and in vitro metabolism of different classes of drugs and subnormal baseline concentrations of various components of the hepatic drugmetabolizing enzyme system (10)(11)(12). With the identification in the 1980s of the multiple isoforms of P450 (designated with the initial letters CYP) it became apparent that males were more susceptible to aging-induced declines in drug metabolism than were females.…”
supporting
confidence: 89%
“…Atorvastatin has a long half-life (approximately 14 hours) allowing its administration at any time of day [6], with active metabolites effective for 20-30 hours [5,6]. This makes it an ideal candidate for alternate-day dosing [7,8]. In addition to many helpful effects of statins, they are among the more expensive drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Females tend to have a higher percentage of body fat, which affects the volume of distribution of some drugs and can significantly increase the half-life of a variety of medications, including the more lipophilic statins [16]. A study investigated the effects of sex/gender on the pharmacokinetics of Atorvastatin after administration of 20 mg tablets [39]. The equivalent maximum concentration (Cmax) of Atorvastatin was 17.6% higher in women than in men.…”
Section: Sex/gender Disparities In Statin Utilization From Clinical Pmentioning
confidence: 99%
“…The equivalent maximum concentration (Cmax) of Atorvastatin was 17.6% higher in women than in men. In addition, the mean area under the concentration-time curve (AUC0-infinity) and half-life (t1/2) were 11.3% lower and 19.9% shorter, respectively, in women than in men [39]. In a Chinese study, a pharmacokinetics study was conducted on 12 volunteers following a single dose of 1 mg, 2 mg and 4 mg of Pitavastatin [40].…”
Section: Sex/gender Disparities In Statin Utilization From Clinical Pmentioning
confidence: 99%